Students during the second six weeks of the 1935-36 Spring quarter. - Unknown:::Creator::::::::::::
Written on verso:"Spring Quarter 1935-1936; 2nd 6 weeks Lucille Kable, Elizabeth Foulke, Ursual Culbert, Dorothy Haas."